2021
DOI: 10.3389/fpsyg.2021.652627
|View full text |Cite
|
Sign up to set email alerts
|

Dreaming in Adolescents During the COVID-19 Health Crisis: Survey Among a Sample of European School Students

Abstract: According to the continuity hypothesis of dreaming and contemporary psychodynamic approaches, dreams reflect waking life. The aim of the present study was to explore the relationship between the COVID-19 pandemic and dreaming in adolescents. A cross-sectional survey was conducted in Italy, Romania and Croatia involving 2,105 secondary school students (69% girls, mean age 15.6 ± 2.1 years; 31% boys, mean age 15.1 ± 2.2 years; mean age of whole sample 15.4 ± 2.1 years). No substantial differences between countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…Changes in oneiric phenomenology during the pandemic compared to a non-pandemic condition were assessed with different methods: direct questions about the perception of pandemic-related changes in dreams ( Schredl and Bulkeley, 2020 , Guerrero-Gomez et al, 2021 ) and nightmares ( Pesonen et al, 2020 , Guerrero-Gomez et al, 2021 ), retrospective scoring of dream features ( Conte et al, 2022 , Gorgoni et al, 2021a , Fränkl et al, 2021 , Solomonova et al, 2021 , Scarpelli et al, 2022b ) and nightmare features ( Musse et al, 2020 , Solomonova et al, 2021 , Scarpelli et al, 2022b ) before and during the pandemic, comparison with a population-based pre-pandemic sample ( Scarpelli et al, 2021a , Kilius et al, 2021 ), and comparison with a non-pandemic control group ( MacKay and DeCicco, 2020 , Mota et al, 2020 , Wang et al, 2021 ). Changes in dream frequency during the pandemic in the general population were reported by several studies ( Schredl and Bulkeley, 2020 , Conte et al, 2022 , Gorgoni et al, 2021a , Fränkl et al, 2021 , Scarpelli et al, 2021a , Solomonova et al, 2021 , Scarpelli et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in oneiric phenomenology during the pandemic compared to a non-pandemic condition were assessed with different methods: direct questions about the perception of pandemic-related changes in dreams ( Schredl and Bulkeley, 2020 , Guerrero-Gomez et al, 2021 ) and nightmares ( Pesonen et al, 2020 , Guerrero-Gomez et al, 2021 ), retrospective scoring of dream features ( Conte et al, 2022 , Gorgoni et al, 2021a , Fränkl et al, 2021 , Solomonova et al, 2021 , Scarpelli et al, 2022b ) and nightmare features ( Musse et al, 2020 , Solomonova et al, 2021 , Scarpelli et al, 2022b ) before and during the pandemic, comparison with a population-based pre-pandemic sample ( Scarpelli et al, 2021a , Kilius et al, 2021 ), and comparison with a non-pandemic control group ( MacKay and DeCicco, 2020 , Mota et al, 2020 , Wang et al, 2021 ). Changes in dream frequency during the pandemic in the general population were reported by several studies ( Schredl and Bulkeley, 2020 , Conte et al, 2022 , Gorgoni et al, 2021a , Fränkl et al, 2021 , Scarpelli et al, 2021a , Solomonova et al, 2021 , Scarpelli et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…The COVID‐19 pandemic has affected sleep and dreams for many individuals and has been linked to changes in mental health, lifestyle habits and social interactions (Pérez‐Carbonell et al, 2020 ; Shillington et al, 2021 ). Insomnia severity during this time has been linked to suicide ideation (Killgore et al, 2020 ) and much of the anxiety and stress associated with health and general well‐being has played out in dreams and nightmares with pandemic‐related themes (Guerrero‐Gomez et al, 2021 ; MacKay & DeCicco, 2020 ; Mota et al, 2020 ; Ruby, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This was also seen in a Brazilian study that analyzed dream themes and found a higher proportion of themes around contamination and cleanliness (Mota et al, 2020), and in a Finnish study where participants reported more night-time awakenings and nightmares as compared to pre-pandemic times, with over 50% of these nightmares about pandemic-specific themes, including sickness, physical distancing and family concerns (Pesonen et al, 2020). Among adolescents living in Italy, Croatia and Romania, an increase in nightmares and dreams with pandemic-related themes were also reported (Guerrero-Gomez et al, 2021).…”
mentioning
confidence: 96%
“…As Covid-19-related worries were not related to dream recall frequency, it is very likely that the subjectively reported increases in dream recall frequency due to the pandemic ( Fränkl et al, 2021 ; Guerrero-Gomez et al, 2021 ; Schredl & Bulkeley, 2020 ; Solomonova et al, 2021 ) might not be explained by direct effects of the pandemic itself on dream life but by indirect effects, for example, changes in sleep behavior due to lock-downs ( Gorgoni et al, 2021 ; Scarpelli et al, 2021 ), e.g., home schooling and home office increased sleep duration in some parts of the population ( Bottary et al, 2020 ) whereas, on the other hand, sleep problems including more frequent nocturnal awakenings were also reported more often during the pandemic ( Dal Santo et al, 2021 ). That is, longer sleep duration ( Schredl & Fulda, 2005 ), on the one hand, and insomnia and frequent nocturnal awakenings ( Schredl et al, 1998 ), on the other hand, are related with higher dream recall frequency.…”
Section: Discussionmentioning
confidence: 98%
“…The main objective of the present study was to investigate the relationship between the Big Five personality factors, dream recall frequency, and lucid dream frequency in a new and independent sample. However, as the survey was carried out during the Covid-19 pandemic, we had the opportunity to explore whether the presence and intensity of Covid-19-related anxiety is related to dream recall frequency and/or lucid dream frequency as a substantial number of studies ( Fränkl et al, 2021 ; Guerrero-Gomez et al, 2021 ; Schredl & Bulkeley, 2020 ; Solomonova et al, 2021 ) reported an increased dream recall frequency due to the pandemic in a substantial percentage of the population. For focusing on the main objective of the study, we included this COVID-19 related variable in the regression analysis in order to control for possible confounding effects.…”
mentioning
confidence: 99%